2019
DOI: 10.21475/ajcs.19.13.11.p1886
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical composition of pigeonpea genotypes in Kenya

Abstract: Pigeonpea is an important crop in semi-arid tropics and sub-tropics. The improvement and utilization of this crop in East Africa can enhance food and nutrition security. A study was carried out to examine variation in biochemical composition (crude protein, total phenols, total flavonoid and total anti-oxidant activity) of 55 pigeonpea genotypes grown in Kabete field station during the long rains of April-September 2017. The experiment was set up in a randomized complete block design with three replications. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(22 reference statements)
0
2
1
Order By: Relevance
“…Combined with relatively low cost and wide access to the poor, pulses are characterized as "poor man's meat" (Malo and Hore, 2020). The variability observed for whole-grain protein in the present study (23.35-29.50%) was higher than the protein content (16.76-26.82%) reported in previous studies (Amarteifio et al, 2002;Sekhon et al, 2017;Obala, 2018;Cheboi et al, 2019;Choi et al, 2020;Jawalekar et al, 2020) and is comparable with the dhal protein content of high protein lines (27-29%; Saxena et al, 1987). The protein content in dhal is higher than that in the whole grain (Susmitha et al, 2022), signifying that dhal nutritional analysis of the superior accessions in this study may still have higher protein than the high protein lines reported by Saxena et al (1987).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Combined with relatively low cost and wide access to the poor, pulses are characterized as "poor man's meat" (Malo and Hore, 2020). The variability observed for whole-grain protein in the present study (23.35-29.50%) was higher than the protein content (16.76-26.82%) reported in previous studies (Amarteifio et al, 2002;Sekhon et al, 2017;Obala, 2018;Cheboi et al, 2019;Choi et al, 2020;Jawalekar et al, 2020) and is comparable with the dhal protein content of high protein lines (27-29%; Saxena et al, 1987). The protein content in dhal is higher than that in the whole grain (Susmitha et al, 2022), signifying that dhal nutritional analysis of the superior accessions in this study may still have higher protein than the high protein lines reported by Saxena et al (1987).…”
Section: Discussioncontrasting
confidence: 82%
“…Nutritionally, pigeonpea grain is rich in protein, Ca, Mn, and crude fiber (Saxena et al, 2010). The variability for protein content, reported in previous studies, varied from 16.7 to 26.8% (Amarteifio et al, 2002;Sekhon et al, 2017;Obala et al, 2018;Cheboi et al, 2019;Choi et al, 2020;Jawalekar et al, 2020), whereas, in wild species, the range is from 16.3 to 33.8% (Upadhyaya et al, 2013). Very few studies enumerated mineral composition in pigeonpea (Singh et al, 1984;Oshodi et al, 1993;Amarteifio et al, 2002;Mishra and Acharya, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, these values vary with genotype and across different studies ( Talari and Shakappa, 2018 ). Biochemical evaluation of a total of 55 genotypes comprising advanced lines, improved cultivars, and landraces resulted in the identification of variation in four parameters: crude protein content (16.7%–28.4%), total phenol (21.9–84.4 mg/100 g), total flavonoid (16.4–33.4 mg/100 g), and total antioxidant activity (19.2–82.5 mg/100 g) ( Cheboi et al, 2019 ).…”
Section: Utilization Of Grain Legume Germplasm For Crop Improvementmentioning
confidence: 99%